THE ROLE OF TEMPERATURE IN REGULATING CHRYSANTHEMUM FLOWER COLORATION FOR THE OPTIMIZATION OF FLORICULTURE PRODUCTION - Febry Nurhidayati; Gen Adi Wisanggeni; Anditya Gilang Rizky P; Rehino Yanu Seto (Bajang Institute, 2025)
The coloration of chrysanthemum flowers is strongly affected by ambient temperature, primarily through the biosynthetic and degradative pathways of anthocyanin pigments. This literature review synthesizes findings from 2015 to 2025, focusing on temperature effects under both open-field and controlled-environment (greenhouse) conditions. Elevated temperatures (≥30 °C) have been shown to inhibit anthocyanin biosynthesis and accelerate pigment degradation, leading to faded petal coloration. Conversely, cooler temperatures promote pigment accumulation, resulting in brighter and more persistent floral hues. These temperature-dependent responses vary across cultivars and are influenced by developmental stages and interactions with light intensity, relative humidity, and nutrient status. Greenhouse cultivation offers potential mitigation but demands integrated microclimate regulation. Omics approaches, including transcriptomics and metabolomics, hold promise in uncovering the genetic mechanisms that regulate flower coloration. In parallel, the application of smart technologies such as the Internet of Things (IoT) and big data, driven prediction systems can support precision cultivation practices. These insights provide a scientific foundation for optimizing chrysanthemum-based floriculture production systems that are resilient to climate change